Juridical Analysis Related To The Harmonization Of Lahat Regional Goverment Policy On Childfriendly District With Legal Protection Of Exploitation Of Child Workers In Lahat Palm Oil Industry In Terms Of Law Number 13 Of 2003 Concerning Manpower And Lahat District Regulation Number 2 Of 2020 Concerning Childfriendly Districts (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the harmonization of the Lahat Regional Government’s policy on Child Friendly District (KLA) with legal protection against child exploitation in the palm oil industry in Lahat Regency, as well as the extent to which the application of Law Number 13 of 2003 concerning Manpower and Lahat Regency Regional Regulation No. 2 of 2020 concerning Child Friendly District can overcome the problem of child labor in the sector. The research method used is normative juridical, with a statutory approach and analysis of relevant regulations and conceptual approaches. The results show that although there is a KLA policy in Lahat District that focuses on child protection, the implementation of protection against child labor in the palm oil industry still faces challenges, especially in terms of supervision and law enforcement. Harmonization between the Lahat District Regulation No. 2 of 2020 and the Manpower Law needs to be strengthened to ensure that local government policies not only support the Child Friendly District, but also provide maximum protection to children involved in risky work sectors, such as in the palm oil industry. This research suggests the need for better synergy between the local government, law enforcement agencies, as well as the private sector to address the issue of child exploitation and create a safe and decent working environment for children in Lahat District.